The Influence of Digital Social Networks on Contemporary Cuban - Izquierdo Cuellar, Yolier (Multidisciplinar (Montevideo), 2025)
The article addresses the relationship between digital social networks and democracy in the contemporary Cuban context. From a theoretical perspective, key concepts of democracy are explored, according to authors such as Plato, and contrasted with the Cuban political system. The arrival of information and communications technologies has profoundly modified social interaction, promoting the exercise of the right to freedom of expression. However, in the case of Cuba, this phenomenon represents a challenge for the government, which faces citizen discontent reflected in social networks and the proliferation of critical digital media. The Cuban sociopolitical situation, influenced by the US embargo, has generated uncertainty about the nature of its political system, described as totalitarian by some and democratic by others. Social networks have allowed citizens to express their dissatisfaction and organize themselves, as occurred in the protests of 2021. These platforms represent a new space for democratization and political participation, although they also pose challenges for the government, such as the management of disinformation and public criticism.